THE MULTI-LEVEL GOVERNANCE OF INTERNATIONAL MIGRATION - Ivan A. Aleshkovskii (Модернизация, инновация, развитие)
Article retractedThe article provides the history of legal framework of regulating migration processes on the global level. The author analyzes the dual nature of migration policy on the regional, national and global levels, which occurs when interests of different parties involved in international relations do not coincide. Recommendations are given on ways to improve the regulation of migration processes.